INTERNALIZATION OF GENDER EQUALITY VALUES IN SOCIOLOGY LEARNING - Widiyanti, Sopi Aprilia; Malihah, Elly; Wilodati, Wilodati (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
This research is motivated by the existence of gender bias practices carried out by students. The main aim of this research is to analyze the role of teachers at SMAN 9 Bandung City when internalizing gender equality values in sociology learning as an effort to minimize gender bias practices and form the character of students who are sensitive and care about gender equality in everyday life.Internalizing the value of gender equality is a process where a person begins to accept and understand the values, norms, principles related to gender and apply them in the community environment. This research was conducted through interviews, observations and documentation studies using a qualitative approach with a strategy in the form of case studies of Sociology Teachers, Guidance and Counseling Teachers and class XI students. Based on this researcht we can know,Sociology teachers strive to implement learning methods that can increase the participation of male and female students equally. On the other hand, sociology teachers try to use interactive learning media such as video shows, images, PowerPoints that reflect gender equality. Then the sociology teacher tries to correlate relevant material with gender equality issues, such as material on social differentiation, social stratification and various social phenomena. By internalizing the value of gender equality, it increases students' ability to understand the meaning of gender equality values, students' understanding of gender equality is also reflected in the character of students who are shown in making decisions based on common interests, mutual respect and support for each other, participation of male students. -men and women become more equal.